Synthesis and Properties of Benzocyclobutene-Functionalized Perylene Bisimide - Xu, Yewei; Tang, Jie; Zhu, Fanghua; Zhang, Lin (Asian Journal of Chemistry, 2012)
Benzocyclobutene-functionalized perylene bisimide (PBI 4) has been synthesized via Suzuki coupling reaction and its structure was characterized by FTIR, MS and NMR. The thermal and optical properties have been determined by thermogravimetric analyses, differential scanning calorimetry, UV/VIS and fluorescence spectroscopy. The results showed that PBI 4 has thermopolymerization property, which can react either with itself or the appropriate dienophiles to form the corresponding polymers under appropriate temperature. The polymer resin possessed good film planarization in the white-light interferometry photo and the process of oligomer curing on a wafer was no fusion and flow. These results indicated that PBI 4 is a promising film material.